Ontario conservation authorities – end, evolve, interlude or epiphany?. Issue 3 (3rd July 2021) - Mitchell, Bruce; Shrubsole, Dan; Watson, Nigel
Abstract: Ontario Conservation Authorities (CAs) were established in 1946 as a partnership between the Ontario provincial government and municipalities. Initially, their purpose was to apply a catchment or watershed approach to provide services and programs to reduce risk from flooding and erosion through an integrated approach to water and land management. In 2021, there are 36 Conservation Authorities. We consider key changes the Ontario Government has initiated or will be initiating related to CAs which are: (1) The relevant provincial Minister will have authority to approve specific development proposals or for an entire class of permits for a specified period of time in areas within CAs, even if the CAs oppose such development because the proposals involve areas vulnerable to flooding or other related hazards; and (2) Applicants for development permits will be able to appeal directly to the Provincial Minister and also the Local Planning Appeal Tribunal (LPAT) if their application is turned down by the Hearing Board of the relevant CA. This commentary describes key issues that have been historically noted as 'problematic' for previous and the current Provincial Governments, and shares information and insight on those matters. The conclusion considers whether the changes represent an end, an evolution, an interlude (an intervening period, an opportunity to recalibrate or refocus) or an epiphany (a moment of insight or understanding), or some combination thereof, for the CAs.